Ka Rangona te Reo: The Development of Māori-language Television Broadcasting in Aotearoa New Zealand - Middleton, Julie (Te Kaharoa, 2010)
New Zealanders today can hear Māori language broadcast in a variety of contexts: on Māori Television and to a lesser extent on state-owned TV1, TV2 and privately-held TV3, on digital platforms and via broadcasters’ programmes-on-demand internet sites. However, these opportunities are a relatively recent development spurred by years of agitation by Māori about the decline of te reo Māori in an English-saturated world and the recognition that the powerful medium of television broadcasting could help promote, protect and enhance reo and tikanga.